"Burkini" bans in Belgian municipal swimming pools: Banning as a default option. Issue 4 (December 2018) - Brems, Eva; Chaib, Saïla Ouald; Vanhees, Katrijn
Muslim women's religious dress is a matter that exercises many minds and the recent public debate on the so-called "burkini" (preferably phrased as "body covering swimwear") is the umpteenth variation on the theme. Following the French commotion on the presence of "burkini" wearers at the coast in 2016, the "burkini" became the subject of public debate in Belgium. Whereas the "burkini" did not cause much public unrest in the context of the Belgian coast, the majority of local swimming pools in the Flemish region of Belgium do have dress codes banning the "burkini", even before the (inter)national media outcry. This article discusses the prevalence of these restrictive dress regulations and scrutinizes the rationalisation behind local "burkini" bans in municipal swimming pools. These findings are complemented with the perspectives and experiences of "burkini" wearers, who challenged the "burkini" bans before the court. Finally, this article analyses the "burkini" bans in light of European human rights standards.